Research of influence of technological parameters of process of strengthening of metals by method of carbonitriding in smouldering digit on wearproofness - Каплун, В.Г.; Паршенко, К.А.; Паршенко, А.В. (Problems of Tribology, 2014)
The results of investigations of the influence of technological parameters of the process of strengthening metals by carbonitration in a glow discharge on the wear resistance are given. It is proved that the basic parameters of the process in a glow discharge carbonitration significantly affect the thickness of the nitrided layer and the microhardness of the samples. The optimal mode carbonitration in a glow discharge for maximum wear resistance of steels investigated